Barriers to Healthcare Participation in Persons With Disabilities in Appalachia: A Qualitative Pilot Study. (October 2018) - Kurowski-Burt, Amy; Haddox, John Christopher
Objectives: A study exploring facility-related barriers to healthcare participation (the level to which an individual is engaged or involved in their own healthcare activities from simply keeping appointments to following treatment regimens) in persons with disabilities in Appalachia from the perspectives of four stakeholder groups, (1) adults with disabilities, (2) caregivers of persons with disabilities, (3) advocates for persons with disabilities, and (4) providers who treat persons with disabilities. Background: Persons with disabilities potentially face additional barriers to healthcare participation than those without disabilities. Understanding and addressing the barriers to participation could assist in improving healthcare outcomes among the disabled population. Methods: A qualitative study was conducted involving scripted focus groups with four stakeholder groups with expertise/experience in disabilities. The objective was to assess perceptions of impacts of clinical design elements on healthcare participation. Results: Participants identified and characterized six major categories of facility- and nonfacility-related barriers they felt impacted healthcare participation, with priority differences reported between each group. Conclusions: The healthcare facility is perhaps the most visible tool the provider has at his or her disposal to deliver effective healthcare. Understanding the interactions persons with different disabilities have with the physical facility and the messages, both intentional and unintentional, the state of the facility sends can provide useful insights into delivering more effective healthcare to this population.